Study of nutritional factors in food allergies and food intolerances : in the framework of the agriculture and agro-industry including fisheries programme, adopted by the Council of Ministers of the European Communities - Ortolani, Claudio; Pastorello, Elide Anna; Ansaloni, Raffaella; Incorvaia, Cristoforo; Ispano, Marco; Pravettoni, Valerio; Rotondo, Federica; Scibilia, Joseph; Vighi, Giuseppe (European Commission, 1997)
A collection of studies that focused on the role of nutrition on food allergies and intolerances. Intended for professional public.
Science research development, ISSN 1018-5593
Keywords: alergologie a imunologie; Food Intolerance; Nutritional Sciences; potravinová intolerance; nutriční vědy; nutriční terapie, dietoterapie a výživa; fyziologie výživy; Nutritional Physiological Phenomena; Food Hypersensitivity; potravinová alergie